The Methodology of Teaching Young Children from Kindergarden - O. S, Solijonova; B. U, Erkinova (International Journal of Human Computing Studies, 2022)
Language teaching is one of the most significant phenomenon in educational system of Uzbekistan. As English is becoming a global language, The necessity to teach it from early age has been increased drammatically. This article will illustrate how to teach kids, how to attract, how instructors make children interestedK